Child-Adult Interaction: Orientation of Children's Initiative - Shur S.E.; Zuckerman G.A. (Психологическая наука и образование, 2022)
The purpose of our work was to establish diagnostic criteria for assessing how the child interprets the proposed form of interaction in a situation where an adult sets an intellectual task and offers help. In this case study, we described two productive children’s strategies for redefining the situation of interaction. Some children prefer to act independently of their partner putting forward and testing their own assumptions about the way to solve the task, whereas others consider the offer for help as an effective way to find out through questioning the missing conditions of action. Nevertheless, our diagnostics showed that in today’s school, the proactive actions of children (targeted primarily at the content of the task and / or at the partner) are registered in less than a half of the 3—4 graders. We believe that one of the goals of activity-based education is to expand the proactive repertoire of each student in a situation of an intellectual task and to alleviate the tendency to discard his own initiative by lingering instead on ready-made answers and instructions by the adult and by yielding at the first failure. This goal will be met more successfully when the teacher takes into account that the children who come to school have already developed their favored attitudes for interaction when an adult sets a new task.